Development of Ibis Paint X-Based Learning Video Media on Metamorphosis Content to Improve Students’ Understanding of Third Grade Elementary School - Intan Dihni Arsika; Novanita Whindi Arini (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Science learning in elementary schools often faces challenges, particularly in students' difficulty understanding the material. These difficulties stem from a lack of interest in learning due to the unappealing learning media used in class. This problem certainly requires a relevant solution. The use of engaging learning media, such as instructional videos, can be utilised in learning. These instructional videos can be developed using various platforms, one of which is Ibis Paint X. The purpose of this study is to develop educational videos as learning media for science instruction in third-grade. Methodology: The research method employed is Research and Development (R&D), utilising the ADDIE Model, which comprises five stages: analysis, design, development, implementation, and evaluation. Findings: Based on the results of the validity test, the assessment of media experts obtained (79%) with the criteria of "feasible", (80%) from material experts with the criteria of "feasible", (90%) from education experts with the criteria of "very feasible", (92%) from small trials with the criteria of "very feasible", and (92%) from large trials with the criteria of "very feasible". The pre-test score is (57%) and the post-test score is (71%); the assessment shows an increase in student understanding by (14%). Based on the research results, it is evident that there was an increase in students' understanding of the material. Furthermore, during the learning process, it was also observed that students were interested in the media presented, which made them more focused on the learning activities. Contribution: The results of this study contribute to the development of effective video-based learning media that improve third-grade students' understanding of animal metamorphosis